How do you solve e^(4x-1)=(e^2)^x e4x−1=(e2)x? Precalculus Solving Exponential and Logarithmic Equations Logarithmic Models 1 Answer Konstantinos Michailidis · Stefan V. Sep 9, 2015 x=1/2x=12 Explanation: Well it is e^(4x-1)=e^(2x)=>e^(4x-2x-1)=1=>e^(2x-1)=1=>2x-1=0=>x=1/2e4x−1=e2x⇒e4x−2x−1=1⇒e2x−1=1⇒2x−1=0⇒x=12 Answer link Related questions What is a logarithmic model? How do I use a logarithmic model to solve applications? What is the advantage of a logarithmic model? How does the Richter scale measure magnitude? What is the range of the Richter scale? How do you solve 9^(x-4)=819x−4=81? How do you solve logx+log(x+15)=2logx+log(x+15)=2? How do you solve the equation 2 log4(x + 7)-log4(16) = 22log4(x+7)−log4(16)=2? How do you solve 2 log x^4 = 162logx4=16? How do you solve 2+log_3(2x+5)-log_3x=42+log3(2x+5)−log3x=4? See all questions in Logarithmic Models Impact of this question 3788 views around the world You can reuse this answer Creative Commons License